Bonicula : una historia de misterio conejil - Howe, Deborah; Howe, James, 1946-; Nava Bouchain, Francisco (Mexico : Fondo de Cultura Economica, 1994)
Though scoffed at by Harold the dog, Chester the cat tries to warn his human family that their foundling baby bunny must be a vampire.
Translation of: Bunnicula.
"Para los que leen bien"--P. [4] of cover.
Keywords: Rabbits -- Juvenile fiction; Vampires -- Juvenile fiction; Bunnicula (Fictitious character) -- Juvenile fiction; Spanish language materials; Literatura infantil y juvenil -- Traducciones del ingles